PENGARUH KONSELING GIZI TENTANG KONSUMSI DAUN KATUK DAN KACANG HIJAU DENGAN MEDIA BOOKLET TERHADAP PERILAKU IBU MENYUSUI DI KECAMATAN PERCUT SEI TUAN - Ratna Zahara; Lusyana Gloria Doloksaribu; Rohani Retnauli Simanjuntak (Poltekkes Kemenkes Medan, 2021)
ABSTRACT Breastmilk (ASI) is the best life fluid that is needed by babies, containing various important substances for the baby's growth and development according to their needs. The success of breastfeeding is influenced by the nutrients consumed by the mother during pregnancy and breastfeeding. This study was conducted to determine the effect of breastfeeding counseling using bookletters on breastfeeding behavior in Percut Sei Tuan District. This type of research is a quasi-experimental (Quasy experiment) with a pre-test research design and a post-test design with a comparison group. Conducted in March - August 2020, the samples were breastfeeding mothers in Percut Sei Tuan District in Cinta Rakyat Village as an intervention group and breastfeeding mothers in Cinta Damai Village as a comparison group. Samples and controls were selected by